Collaborative action research for middle grades improvement. Issue 2 (2nd April 2016) - Downes, John M.; Bishop, Penny A.; Swallow, Meredith; Olofson, Mark; Hennessey, Susan
Abstract : Technology's rapid evolution applies constant pressure to educational organizations, suggesting a need to continually re-envision schools for the digital age. Yet educators often struggle to understand the growing chasm between students' out-of-school and in-school technology lives. This gap is particularly noticeable during the middle grades years, when home technology use increases dramatically. The purpose of this research was to examine the experiences of teachers and students engaged in collaborative action research for middle school improvement in technology-rich settings. We begin by outlining our theoretical framework, emphasizing Fletcher's Ladder of Student Involvement. We then describe our case-study design and methods. Findings are organized by action research components and a discussion of key themes follows. Finally, we consider the implications of this study for action research as a means of student involvement and teacher learning.